Language Style used in “ Achieving Eco Tourism in Bali: Making Bali Future-Proof” Now! Bali Podcast - Oktaviani, Ketut Widia; Warmadewi, Anak Agung Istri Manik; Kade Claria, Dewa Ayu (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
The title of this study is "Language Style Used in the Podcast 'Achieving Eco Tourism in Bali: Making Bali Future Proof' Now! Bali." The language styles used in the podcast are discussed in this study. The theory applied in this study is Joos' language style theory (1967). A qualitative method with a descriptive approach is employed in this study. In this process, several steps are taken, including data collection from the podcast, transcription of conversations, data analysis, and presentation of the analysis results. The data used in this study were obtained from the dialogue in the podcast "Achieving Eco Tourism in Bali: Making Bali Future Proof." Data were collected by listening to the podcast, recording relevant dialogues, and classifying the identified language styles. Based on the results of the analysis, three types of language styles were identified in the podcast, namely formal style, consultative style, and casual style. Meanwhile, frozen and intimate language styles were not found in the conversation, as the context of the discussion was considered more professional and informative. The formal language style is used to align systematic and structured information. The consultative language style is applied in interactive interactions between the host and the guest speaker, while the casual language style is found in more relaxed and informal conversations.